Etiology of severe anemia in Kashmiri children aged 6 months to 6 years - Mir, Naseer Yousuf; Farooq, Wamiq; Wani, Jawad Nazir; Zaman , Bashir U.; Jan, Muzaffar; Ahmad , Kaiser (International Journal Of Community Medicine And Public Health, 2023)
Background: Anemia is said to be present when the hemoglobin level is more than two standard deviations below the mean for the child’s age and sex. Anemia is the most common global nutritional disorder and may lead to psychomotor retardation, low intelligence, decreased learning capability, weakening of immune system and predisposes to serious infections in children. Methods: The study was an observational study. Physical signs of severe anemia were looked in patients attending outpatient department or admitted in hospital. Children with hemoglobin levels <7 gm/dl and in the age group 6 months to 6 years were recruited in study. Results: The study included 192 patients with a male, female ratio of around 1:1. The mean age of the study subjects was 2.2±1.6 years. Most of the patients around 54% belonged to age group of 6 months to 1½ years. Fever was most common presentation in 86 cases (44.77%), followed by diarrhea and easy fatigability in 38 (19.79%) and 21 (10.93%) patients respectively. A total of 76.56% of patients were having nutritional and 23.44% non-nutritional causes. Iron deficiency anemia is most common etiology 115 (59.90%) with 14 patients having celiac disease, 19 cases (9.90%) were diagnosed as megaloblastic anemia, 13 cases (6.77%) were diagnosed as dual deficiency anemia, 30 cases (15.63%) were diagnosed as hemolytic anemia. Conclusions: Nutritional anemia is major cause of anemia in children. Celiac disease, trichuriasis, cow milk protein allergy should be ruled out in iron deficiency anemia patients.